THE USE OF CODE-MIXING ON KEYNOTE SPEAKER OF “ISLAMIC TEACHING FORUM OF PARENTING AND CHILDREN EDUCATION” - Afifah Raihany (IAIN MADURA, 2018)
There are various ways used by the speaker in conveying ideas to the audience. One of them is using code mixing. This is a Descriptive Qualitative research aimed at describing types, kinds, functions, and causal factors of code mixing used by Mrs. Hj. Elly Risman Musa, S.Psi as the keynote speaker of Islamic Teaching Forum of Parenting and Children Education with the topic “How to Communicate with Children” downloaded on Youtube. The data are in the form of oral data from words used by her. Methods used are attentive observing and taking notes. The results revealed that there were other language elements in spoken Indonesia language used by Mrs. Hj. Elly Risman, S.Psi such as the use of Betawi, Dutch, Arabic, and English language. Two types of code mixing found were in the form of words, phrases, clauses, and Basters. The kinds of code mixing are inner and outer code mixing. The functions are as repetition and confirmation; citation; function of the communicant; infixation of sentences; and an element of qualifying the content. The causal factors found are attitudinal and linguistic types. It can be inferred that the use of code mixing is still relevant even in the formal situation.